2019
DOI: 10.1155/2019/2063823
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MicroRNA-15a in Human Cancers: A Meta-Analysis and Bioinformatics

Abstract: Background. Although several studies have proved the relationship between the prognostic value of miRNA-15a and different types of cancer, the result remains controversial. Thus, a meta-analysis was conducted to clarify the prognostic value of miRNA-15a expression level in human cancers. Methods. We enrolled appropriate literature by searching the databases of PubMed, Embase, and Web of Science. Subsequently, we extracted HRs and their 95% CIs and calculated pooled results of miRNA-15a for overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In contrast, many studies have reported that lower expression of miR-15a correlates with poor prognosis in many types of cancer. 51 A meta-analysis of 10 studies containing 1616 patients of 7 cancer types concluded that lower expression of miR-15a significantly predicted adverse OS. 51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, many studies have reported that lower expression of miR-15a correlates with poor prognosis in many types of cancer. 51 A meta-analysis of 10 studies containing 1616 patients of 7 cancer types concluded that lower expression of miR-15a significantly predicted adverse OS. 51 …”
Section: Discussionmentioning
confidence: 99%
“… 51 A meta-analysis of 10 studies containing 1616 patients of 7 cancer types concluded that lower expression of miR-15a significantly predicted adverse OS. 51 …”
Section: Discussionmentioning
confidence: 99%
“…miR-15 was identified for the first time in 2002, together with miR-16, as a potential oncomiR in the pathogenesis of chronic lymphocytic leukemia (CLL), being frequently deleted and/or downregulated in this malignancy [ 112 ]. Recently, Yang et al performed a meta-analysis to assess the prognostic value of miR-15a in human cancers [ 113 ], confirming that this miRNA is frequently downregulated, in particular in NSCLC [ 114 ]. Moreover, miR-15a has been found to regulate epithelial-to-mesenchymal transition (EMT) by silencing Twist1 [ 115 ], a key regulator of this process, together with Slug, which has a relevant role in lung carcinogenesis [ 116 ].…”
Section: Sgk1 Is a Predicted Target Of Micrornas Relevant In Nsclcmentioning
confidence: 99%
“…A number of novel prognostic biomarkers for HNSCC have been explored (7)(8)(9). However, none of these has been recommended for routine clinical testing.…”
Section: Introductionmentioning
confidence: 99%